Political communication and disasters: A four-country analysis of how politicians should talk before, during and after disasters. (March 2016) - Ewart, Jacqui; McLean, Hamish; Ames, Kate
Abstract: Politicians are increasingly involving themselves in the frontline delivery of information in the lead up to disasters and as they unfold. They are often placed as spokespeople and represent the public face of disaster, be it anthropogenic or natural. A disaster also offers opportunities for a politician to participate in intense media coverage and build their profile. However, this represents potential conflict within the disaster management environment when a disaster response is being coordinated by senior public servants or emergency response personnel. This paper examines the observations of senior emergency managers about politicians׳ communication with various publics before during and after disasters. Analysis is based on interviews conducted in four countries, Australia, Norway, the United Kingdom and Germany. While emergency managers believe the involvement of politicians in communicating about disasters is important, they would prefer that politicians restrict their activities during the response phase of such events. This paper reviews interview data to reveal the role-based expectations of politicians by emergency managers. Our findings have implications for the management of disasters, and the involvement of politicians in communication about these events.